2016
DOI: 10.3748/wjg.v22.i10.3038
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus and hepatitis C virus play different prognostic roles in intrahepatic cholangiocarcinoma: A meta-analysis

Abstract: HBV infection may indicate a favorable prognosis in patients with intrahepatic cholangiocarcinoma, while HCV infection suggests a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…Specifically, HBV-associated ICCs may have a higher AFP and CA 19-9 levels, tend to have tumour capsule formation, cirrhosis and a lower rate of lymph node metastasis. Two large meta-analyses have shown that HBV was associated with better prognosis, which is consistent with the majority of the studies included in this systematic review, but this association warrants further prospective investigation (44,45).…”
Section: Discussion Discussionsupporting
confidence: 86%
“…Specifically, HBV-associated ICCs may have a higher AFP and CA 19-9 levels, tend to have tumour capsule formation, cirrhosis and a lower rate of lymph node metastasis. Two large meta-analyses have shown that HBV was associated with better prognosis, which is consistent with the majority of the studies included in this systematic review, but this association warrants further prospective investigation (44,45).…”
Section: Discussion Discussionsupporting
confidence: 86%
“…More recently, Tao et al [28] found that prothrombin time was also found to be higher in HBV-associated ICC patients (P = 0.030), complementing the studies from Zhou et al [42] and Peng et al [27]. The above mentioned clinicopathological characteristics of HBV-associated ICC were verified by a meta-analysis that involved 14 studies and 2842 cases [43]. HBV infection was more frequent in male patients [odds ratio (OR) = 1.91, 95% confidence interval (CI) = 1.06 to 3.44] and was correlated with elevated serum aspartate transaminase (AST) (OR = 1.93, 95%CI = 1.11 to 3.35) and AFP levels (OR = 3.86, 95%CI = 2.58 to 5.78), as well as a relatively lower level of serum CA19-9 (OR = 0.47, 95%CI = 0.34 to 0.65) [43].…”
Section: Clinicopathological Characteristicsmentioning
confidence: 76%
“…The above mentioned clinicopathological characteristics of HBV-associated ICC were verified by a meta-analysis that involved 14 studies and 2842 cases [43]. HBV infection was more frequent in male patients [odds ratio (OR) = 1.91, 95% confidence interval (CI) = 1.06 to 3.44] and was correlated with elevated serum aspartate transaminase (AST) (OR = 1.93, 95%CI = 1.11 to 3.35) and AFP levels (OR = 3.86, 95%CI = 2.58 to 5.78), as well as a relatively lower level of serum CA19-9 (OR = 0.47, 95%CI = 0.34 to 0.65) [43]. In addition, there were significant differences in the incidence of liver cirrhosis (OR = 6.44, 95%CI = 4.33 to 9.56), capsule formation (OR = 6.04, 95%CI = 3.56 to 10.26), and lymph node metastasis (OR = 0.39, 95%CI = 0.25 to 0.58).…”
Section: Clinicopathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Original studies that reported associations between HCV infection and hepatic and extrahepatic malignancies are summarized in Supporting Information Table 1. The strength of the evidence supporting associations between HCV infection and cancer is presented in Table and in previous meta‐analyses …”
Section: Associations Between Hcv Infection and Cancermentioning
confidence: 99%